Practice of social entrepreneurship among the Muslim entrepreneurs in Malaysia - Mhd. Sarif, Suhaimi; Sarwar, Abdullah Al-Mamun; Ismail, Yusof (IDOSI Publications, 2013)
The issue of social entrepreneurship got immense importance in the eyes of the researchers recently. Moreover, data are very limited in the context of Malaysia especially for Muslim entrepreneurs. Realizing these current needs and trends, this study aimed at understanding the current level of practice of social entrepreneurship among the Muslim entrepreneurs in Malaysia. This study has conducted total five in-depth interviews of various Muslim social entrepreneurs to reveal the entrepreneurial dimension that is prevailing in the non-profit organizations. Moreover, this study addresses the research gap and proposes a model of social entrepreneurship for Muslim social entrepreneurs. To end with, this study summarized that, social enterprises have a valuable role to play in creating and sustaining civil society, the benefits of which are consumed by the whole of society. It is in society’s interest therefore to ensure that their contribution in this respect is protected.